(untitled) (Global Journal of Medical Research, 2024)
Introduction: Nowadays, ozone plays an important role in wound healing and tissue repair as a therapy and as antimicrobial, bactericidal and fungicidal agent. It attains recognition in hair transplantation as a treatment for necrosis due to hypoxic-ischemic local syndrome. Objective: to demonstrate the therapeutic evolution of ischemia in a hair transplant after ozone therapy sessions. Methods: The patient was evaluation and gave consent to photographic records. He went through 30 topic applications of ozonated oil, with a 10 drop dosage daily; 12 bag ozone sessions for 10 minutes; besides subcutaneous applications, with 30% ozone concentration and a very small gas volume (1-2 ml) with 30G needle. Results: Evolution of the case was registered with images and tissue coloring and changes evidenced. Conclusion: It is clear that ozone therapy made wound healing and tissue repair faster, since there was an increase of epithelial cells and neoangiogenesis due to therapy, resulting in almost complete repair of the patient’s hair transplant at the end of the sessions.